The Challenges of Diagnostic and Management of Acute Heart Failure From Hemodynamic Subset to Appropriate Treatment - I Gede Sumantra (Universitas Wijaya Kusuma Surabaya, 2014)
Acute heart failure (AHF) is a common and growing medical problem associated with major morbidity and mortality. Despite the high prevalence of this condition and its associated major morbidity and mortality, diagnosis can be difficult, and optimal treatment remains poorly defined. Identification of the acute triggers for the decompensation as well as characterization of cardiac filling pressures and output is central to management. Evaluation of patients with Heart Failure (HF) is critical for the appropriate selection and monitoring of therapy as well as for the prevention of recurrent hospitalizations.Diagnostic and management AHF is a challenge because of the heterogeneity of the patient population, the existence of a universal definition of understanding, not understanding the pathophysiology, and the lack of bases guideline Evidence-based medicine